Mapping the Research Landscape of Greenhouse Gases: A Bibliometric Approach - Nur Faizaturrohmah; Mia Erpinda; Suci Wulandari (Jurnal Serambi Engineering, 2025)
Greenhouse gas (GHG) emissions are the primary driver of climate change and have become a significant concern in recent decades due to their increasing atmospheric concentration. This study aims to systematically review research trends on GHG emissions over the past 20 years using bibliometric analysis. A total of 1,035 articles were analyzed through VOSviewer to map knowledge structure, research dynamics, and emerging topics. The results show that GHG emission research is divided into six main clusters: (1) gas emissions, (2) industrial and waste management, (3) air quality and human health, (4) bioenergy and energy systems, (5) food production, and (6) global climate change mitigation. Research trends indicate a shift from sectoral studies, particularly agriculture and livestock production (2005–2016), to a more integrated and systemic approach involving energy systems, air quality, and human health (2020–2024). The density visualization highlights “gas emission” as the most frequent and central keyword. Moreover, keywords such as "Municipal Solid Waste Treatment," "Energy Production," and "Domestic GHG Mitigation" have emerged as future research hotspots. This study provides a comprehensive overview of GHG emission research developments and offers valuable insights for identifying future research directions and supporting GHG mitigation strategies.